Respon Pertumbuhan Bayam Merah (Amaranthus tricolor L.) terhadap Aplikasi Ekoenzim Kulit Pisang dan Kulit Bawang Merah - Lara Amnesty; Narita Amni Rosadi; Nurlailah Mappanganro (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
Household organic waste such as banana and shallot peels is often discarded without being utilized, even though both contain nutrients and bioactive compounds that have potential as liquid organic fertilizers. The utilization of eco-enzymes derived from organic waste is expected to serve as an environmentally friendly alternative fertilizer to enhance the growth of horticultural crops, including red amaranth (Amaranthus tricolor L.). This study aimed to determine the effect of various concentrations of banana peel and shallot peel eco-enzymes on the growth of red amaranth plants. The research was conducted in the Greenhouse, using a factorial Completely Randomized Design (CRD) with two factors, namely banana peel eco-enzyme (0, 5, 10, and 15 ml/L) and shallot peel eco-enzyme (0, 5, 10, and 15 ml/L), with three replications. The results of the study showed that the ecoenzyme treatment had a very significant effect (p<0.05) on plant height and a significant effect on stem diameter, but had no significant effect on the number of leaves, root length, wet weight, and dry weight of the plant. The best treatment was obtained from the P2B2 combination (banana peel eco-enzyme 10 ml/L and shallot peel eco-enzyme 10 ml/L), which produced the highest plant height of 31.00 cm and stem diameter of 8.33 mm. These findings indicate that eco-enzymes derived from organic waste have great potential as environmentally friendly liquid organic fertilizers to improve the growth of red amaranth plants. Using ecoenzymes at a concentration of 10 ml/L provides an optimal growth response and has the potential to be an environmentally friendly alternative liquid organic fertilizer to increase the growth of red spinach plants.